(untitled) (Research, Society and Development, 2021)
Introduction: Gestational Diabetes Mellitus (GDM) occurs when the body is not efficient at capturing enough glucose to meet extra needs during pregnancy, resulting in hyperglycemia of varying severity, resulting from the total or partial deficit of the hormone insulin. Objective: To perform a literature review on the importance of physiotherapists at the control end no prevention of Gestational Diabetes Mellitus. Methods: This is a literature review. Data were collected in the PEDro, PubMed and Cochrane Library databases. The selected descriptors were: Eclampsia, Physiotherapy, and Gestational Diabetes. The inclusion criteria were complete articles, published in national and international journals, and containing information that responded to the theme of the study. The exclusion criteria involved duplicate publications. Results and Discussions: In the crossing of the descriptors, 17 articles were found, of these, 4 were in the Cochrane Library, 12 in the Public Medline and 1 in PEDro. The studies showed that the patients showed a reduction in the glycemic index. Conclusion: It was concluded that the physiotherapist has a fundamental role in the prevention and control of GDM. Thus, contributing to a better quality of life for pregnant women.